Linking interannual variability of turbidity fronts in the Eastern China Seas to local processes and ocean warming - Du, Yunfei; Fan, Daidu; Zhang, Jicai (Frontiers in Marine Science, 2025)
The turbidity front is susceptible to rapid changes in ocean hydrodynamics. Understanding its variability is crucial for elucidating material transport on continental shelves in light of evolving land-ocean interactions. However, the long-term frontal variability and its controlling mechanism over the shelf sea scale still need further study. Using a decade of satellite observations, this study assesses the interannual variability of turbidity fronts in the Eastern China Seas and their responses to local processes and rapid ocean warming. A gradient-based front detection algorithm and frontal probability are used to identify the geographical locations of turbidity fronts and their variability at the interannual scale, respectively. Regional heterogeneities in interannual variations and controlling mechanisms of frontal activity are observed. Specifically, the significant (p<0.05) and strongest correlations show that wind wave, horizontal temperature gradient, and mixed layer depth are identified as the most important drivers of interannual variations in frontal activity in the Bohai, Yellow, and East China Seas, respectively. The El Niño-Southern Oscillation influences frontal anomalies through a delayed wind-response mechanism (>=4 months). Notably, the recent increase in frontal probability (+0.07%/year) in offshore areas of the Yellow and East China Seas is primarily attributed to an intensified horizontal temperature (density) gradient (+0.0005 °C/km/year) resulting from ocean warming. As ocean warming continues, the offshore transport of terrigenous materials is expected to increase, potentially enhancing ocean primary productivity and carbon sequestration, and altering ecosystem function and fisheries.